Natural history and treatment of craniocervical junction dural arteriovenous fistulas. Issue 11 (November 2015) - Wang, Joanna Y.; Molenda, Joseph; Bydon, Ali; Colby, Geoffrey P.; Coon, Alexander L.; Tamargo, Rafael J.; Huang, Judy
Highlights Eight patients with craniocervical junction dural arteriovenous fistulas (DAVF) evaluated at our institution were reviewed. A systematic literature review of 56 studies with 119 cases was performed. Prompt diagnosis and microsurgical management allows for immediate obliteration. Younger age, hemorrhagic presentation, and microsurgery were predictive of good outcomes.